Localization of the Porion Landmark in Orthodontics: A Comparison of the Efficiency of NEMO-Ceph 2020 Software between Inexperienced and Expert Operators - Loaiza-Martínez, Daniela (2023)
This study discusses the utility of the NEMO-Ceph 2020 software in localizing the cephalometric landmark known as the Porion point (Po) and the Frankfurt plane in orthodontics. It highlights the challenges in locating the Porion point due to anatomical variations and external factors. The use of radiographs as a diagnostic method is mentioned, along with the need for new tools to aid in locating the Porion landmark. The study employed a database of 179 teleradiographs from the "UCAM DENTAL"database, processed using NEMO-Ceph 2020® software. Inexperienced operators (4th and 5th-year dentistry students) and an expert operator participated. Linear measurements and angular differences were analyzed using the software. Results revealed discrepancies in the Porion point's location among operators, with mean discrepancies of 2.42 mm (X-axis) and 2.23 mm (Y-axis). The mean discrepancy between Porion points was 2.47 mm, and with the Frankfurt point was 2.44 mm. No statistically significant correlation existed between discrepancies in the X and Y axes. The study concluded that there was a significant difference in Porion point location between inexperienced operators and the expert, and that NEMO-Ceph 2020® software required expert operators for accurate localization of cephalometric landmarks and could not predict the point independently.